The Evolution of Inflation at the Level of the Danube Region Countries - Bărbulescu, Marinela; Hagiu, Alina; Bâldan, Cristina (Journal of Danubian Studies and Research, 2024)
This paper examines the evolution of inflation in the Danube region over the last five years. Over this period, inflation has been influenced by numerous global and local factors, including the COVID-19 pandemic, geopolitical conflicts, and fluctuations in energy and food prices. The COVID-19 pandemic had a significant impact on inflation, initially reducing it due to falling domestic demand and economic disruptions. As economies recovered, inflation rose, fuelled by rising demand and energy prices. The conflict between Russia and Ukraine added further pressures, especially on neighbouring countries, leading to increases in inflation due to disruptions in supply chains and rising import costs. Monetary and fiscal policies have played a crucial role in managing these fluctuations. EU Member States have benefited from more stable policy frameworks, which have allowed inflation to be managed more effectively. In contrast, non-EU countries have experienced higher fluctuations in inflation due to political and economic instability. Thus, this paper highlights the complexity of managing inflation in such a diverse region and highlights the need for adaptable and well-coordinated economic policies to maintain economic stability. The coming years will continue to present major challenges, and careful monitoring and rapid responses will be essential to ensure sustainable economic growth and stabilize inflation in the Danube region